Influence of Early Strength Agent on the Strength and Water Resistance of Cement-Desulfurized Building Gypsum Composite Cementitious System. Issue 1 (1st January 2022) - Peng, Hong; Lv, Zhong; Zhang, Wenwei
Abstract: The test takes the cementing system composed of ordinary Portland cement and desulfurized building gypsum as the research object, and the research is carried out based on the mechanism of the early strength agent that can accelerate the cement hydration reaction in the composite cementing system. In the experiment, the influence of the type and dosage of the early strength agent on the strength and water resistance of the composite gelling system was studied to determine the appropriate type and optimal dosage of the early strength agent. The test results show that sodium sulfate has a poor improvement effect on the sample due to the presence of desulfurized building gypsum in the composite cementing system, while calcium chloride and calcium formate can effectively promote the hydration of the cement in the composite cementing system, significantly improving the compressive strength and softening coefficient of the sample. When the calcium chloride content is 2%, the compressive strength of the sample is increased by 57.0% compared with the reference sample, and the softening coefficient is 0.82. When the calcium formate content is 1%, the compressive strength of the sample is increased by 31.1% compared with the reference sample, and the softening coefficient is 0.80.